(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the family orientation provided to users of a Basic Health Unit (BHU) located in the city of Lagarto-Se. Methods: This is an observational, analytical, cross-sectional and quantitative study carried out with users older than 18 years, assisted by the Basic Health Unit Dr. Davi Marcos in the municipality of Lagarto, Sergipe. We included people over 18 years of age, residents of the PHU area, who received or are seeking care. We used the Family Orientation component of the Primary Case Assessment Tool (PCATool) - Brazil adult version, besides the analysis according to the Brazil Criterion proposed by the Brazilian Association of Research Companies (ABEP). The Mann-Whitney and Kruskal-Wallis tests were used to verify the association between the sociodemographic variables. Results: The data obtained reflect a mostly female audience with a mean age of 56 years, elementary school education, low income and self-employed. The chronically ill represented 41% of the sample. As for family orientation, a mean score of 4.8 was obtained, classifying it as unsatisfactory, following the same classification when distinguishing between groups of patients and non-patients. Conclusion: The Family Orientation attribute is classified as unsatisfactory in the general public of PHC. In addition, it was seen an audience with the majority women, low income, with occupation of household activity or unemployed. The chronically ill represented a good portion of the population, and this group was also represented by women and those over 60 years of age.